2013
DOI: 10.1126/science.1233000
|View full text |Cite|
|
Sign up to set email alerts
|

Loss of Function of the Melanocortin 2 Receptor Accessory Protein 2 Is Associated with Mammalian Obesity

Abstract: Melanocortin receptor accessory proteins (MRAPs) modulate signaling of melanocortin receptors in vitro. To investigate the physiological role of brain-expressed Melanocortin 2 Receptor Accessory Protein 2 (MRAP2), we characterized mice with whole body and brain-specific targeted deletion of Mrap2, both of which develop severe obesity at a young age. Mrap2 interacts directly with Melanocortin 4 Receptor (Mc4r), a protein previously implicated in mammalian obesity, and it enhances Mc4r-mediated generation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
340
4
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(373 citation statements)
references
References 20 publications
22
340
4
7
Order By: Relevance
“…As with MRAP, MRAP2 also naturally exists as an antiparallel homodimer but with a distinct tissue expression pattern principally in many areas of the CNS (Chan et al 2009, Asai et al 2013, Chaly et al 2016. We demonstrated that MRAP2 interacted with all five of the melanocortin receptors in transfected cells (as does MRAP1) (Chan et al 2009).…”
Section: Mrap2mentioning
confidence: 81%
See 2 more Smart Citations
“…As with MRAP, MRAP2 also naturally exists as an antiparallel homodimer but with a distinct tissue expression pattern principally in many areas of the CNS (Chan et al 2009, Asai et al 2013, Chaly et al 2016. We demonstrated that MRAP2 interacted with all five of the melanocortin receptors in transfected cells (as does MRAP1) (Chan et al 2009).…”
Section: Mrap2mentioning
confidence: 81%
“…Asai and coworkers (Asai et al 2013) demonstrated that under certain transfection conditions, in which a 6:1 ratio of MRAP2 to MC4R expression vector was used, MRAP2 reduced the constitutive activity of the MC4R and enhanced the maximal effect of α-MSH stimulation. As this results in a greater change in signal for a given change in agonist dosage, this can be interpreted as 'sensitizing' the MC4R to agonist.…”
Section: Mrap2mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, MRAP2 does not appear to play a major role in adrenocortical ACTH signalling (Metherell et al 2005). A precise function on MC4R signalling modulation and, consequently, on body weight control, was recently attributed to MRAP2 (Asai et al 2013, Sebag et al 2013. Mrap2 knockout mice are severely obese and weight gain seems to result, in part, from a reduced function of MC4R (Asai et al 2013).…”
Section: Melanocortin System: Receptors Ligands and Accessory Proteinsmentioning
confidence: 99%
“…A precise function on MC4R signalling modulation and, consequently, on body weight control, was recently attributed to MRAP2 (Asai et al 2013, Sebag et al 2013. Mrap2 knockout mice are severely obese and weight gain seems to result, in part, from a reduced function of MC4R (Asai et al 2013). In fact, MRAP2 was found to enhance MC4R signalling in response to a-MSH (Asai et al 2013, Sebag et al 2013, in contrast to the study by Chan et al (2009) that reported a MRAP2 inhibitory effect on MC4R signalling using NDP-a-MSH instead of a-MSH.…”
Section: Melanocortin System: Receptors Ligands and Accessory Proteinsmentioning
confidence: 99%